MARXIST IDEOLOGY IN AUGUSTS DEGLAVS’ NOVEL “THE NEW WORLD” - Genese-Plaude, Inta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The literary texts of Augusts Deglavs (1862-1922) highlight themes of cultural history and sociology and contain a rich spectrum of ideas circulating in the Latvian society of the 19th century. These are ideas of nationalism, capitalism, feminism, Marxism promoted by “New Current” (Jaunā Strāva) movement. The article will analyze the manifestations of Marxist ideas in the novel “Jaunā pasaule”(“The New World”) (1897, 1898). Augusts Deglavs wanted to record and preserve both his own experience and the development and ideas of era. Marxism is a theory about the attitudes of the type of production and social relations. Modern ideas, including Marxism, were captured by Latvian intelligence including Augusts Deglavs. Thus it fits into the discourse of history and perception becomes meaningful directly in the background of the history. He shows the effects of alienation achieved by shock and fragmentation technique.The author depicts the impact of an era’s economic structure on social group attitudes and the life an individual and the cultural formation and consumption